SUN-LB136 A Comparison of Androgen Receptor Splice Variant, AR-V7, and Glucocorticoid Receptor Activity in Prostate Cancer - Dash, Amit K (J Endocr Soc, 2020)
Prostate Cancer (PCa) is an androgen dependent disease and patients with metastatic PCa are treated with androgen deprivation therapy (ADT). Although most tumors respond initially, tumors become resistant and are termed castration resistant prostate cancer (CRPC). There is compelling evidence that most of these tumors retain androgen receptor (AR) dependence and some data to suggest that, in some cases, the glucocorticoid receptor (GR) substitutes for AR. AR, itself, is re-activated through a variety of mechanisms including the expression of constitutively active AR splice variants that lack the ligand binding domain (LBD) of AR. Expression of one variant, AR-V7, which contains the amino-terminal domain and DNA binding domain of AR and 16 unique amino-acids, has been correlated with resistance to second line ADT. Although there has been some debate regarding the role of AR-V7, whether it is only a partial substitute for AR or has unique activities, our studies of engineered cell lines treated to express levels of AR-V7 equivalent to AR, clearly show that while the AR isoforms have common targets, they each also have unique targets. Consistent with this, the cistromes of the two show many unique sites as well as common sites. AR-V7 binding is enriched near the transcription start site (TSS) and we have identified a novel de novo binding motif. These findings suggest the possibility of developing a gene signature unique to AR-V7.Because GR activity in PCa has also been suggested as an escape mechanism in response to ADT, and GR binds to the same consensus response elements, we sought to identify a GR signature in PCa, to compare it with the AR and AR-V7 signatures, and to ask whether the AR-V7 and/or GR signatures are enriched in CRPC. Because much of the gene signatures are cell line dependent, we sought to compare GR and AR-V7 action in cells that express both. LN-95 cells express both AR-V7 and GR. MDA-PCa-2b cells, a cell line derived from an African American patient, expresses GR, but not AR-V7. The parental line was infected with a lentivirus that expresses AR-V7 in response to doxycycline. Transcriptomes were determined for AR, GR, and AR-V7 in these lines using RNA-Seq. Overall the magnitude of regulation of gene expression was generally lower than in the LNCaP AR-V7 and VCaP-AR-V7 lines, but there was good overlap of the MDA-PCa-2b AR-V7 regulated with the LNCaP AR-V7 regulated genes. Genes induced by GR overlapped with AR and isoform common genes, but did not overlap with AR-V7 specific genes. A comparison of AR-V7 specific genes common to the LNCaP and VCaP models as well as to publicly available data sets for LN-95 and 22RV1 AR-V7 signatures, show a strong correlation with CRPC compared to primary tumors when analyzed in the Grasso data set.